Sustainable Value Chain Management : Delivering Sustainability Through the Core Business - D'heur, Michael (CSR, Sustainability, Ethics & Governance,, 2015)
This book introduces the integrated management concept of "Sustainable Value Creation", which delivers sustainability 'inside-out' from the core business. It is based on the premise that sustainability can provide a platform for growth, if it is implemented in a company's products, services and supply chains (combined also known as the 'Value Chain'). Managing the Value Chain from the outset with a sustainability mindset subsequently allows profitable economical, ecological and societal growth. It combines the need for increased sustainability and its implementation in the operations of a company. The book addresses the following issues: How do economic, environmental and societal factors impact the value-creation process of a company? What requirements and expectations need to be met to balance economic, ecologic and societal value creation? What are the building blocks and measures that can be utilized on the journey towards building a sustainable value chain? What benefits can be achieved through sustainable value chains? What are the practical examples of sustainable value chains in leading companies that can inspire others to follow? The book includes contributions from the following organisations and companies: Beiersdorf, SAP, Klenk und Hoursch, VAUDE, Infineon Technologies, Independent Capital Management, BASF, Nanogate, the Federal German Council for Sustainable Development, Henkel, Symrise, shared.value.chain, Siemens, Fairphone and Thin Air Factory.